Influence of Photovoltaic Systems on Power Quality Problems - Sanchez-Puentes, Yohan; Argote-Parra, Christian; Lakatt-Benavides, Waddy; Narvaez-Viana, Jaider; Nuñez-Alvarez, Jose; Grimaldo-Guerrero, John (International Journal of Energy Economics and Policy, 2023)
Photovoltaic (PV) systems have been rapidly implemented in commercial facilities without determining the negative impacts that may result when connected to the facilities’ electrical power system. The research presented shows the results of a study of the quality of electrical energy in a commercial installation in which there were no problems before implementing the PV system. Measurements of different parameters of the energy generated by the photovoltaic system and that provided by the electrical network are carried out, carrying out a simulation using the Helioscope software. As a result of the work, voltage variation and current harmonics problems are identified, carrying out a technical and economic analysis of implementing a passive filter that performs the respective corrective actions.